OUR EXPERIENCE IN HARDING AND «BIKINI» APPROACHES AT TOTAL HIP ARTHROPLASTY - Fil, Adrian; Valihursky, Mykhailo; Dudar, Olexandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Total hip arthroplasty is widely spread in all over the world medical practice. Different approaches are used for that procedure. Objective. To analyze the advantages and disadvantages of` «Bikini» approach and compare them to the Harding approach in patients after total hip arthroplasty. Methods. Тhe results of treatment of 108 patients were retrospectively analyzed: 41 patients were operated with «Bikini» approach, 67 — with Harding approach. Total hip implant with ceramic-on-ceramic, ultra-high molecular weight polyethylene- on-ceramic, and ultra-high molecular weight polyethylene-onmetal movement pair were used, also were used both cemented and cementless types of fixation. Results were evaluated on 14 day and 3 months after the surgery by Harris scale. Results. 14-day of followup the average Harris score value in patients operated with Harding approach were 74.87 points, in patients operated with «Bikini » approach — 80,55 points, on the 3rd month of follow-up period the Harris score was 78.24 and 83.9 respectively. Conclusions. Both evaluated approaches have their own advantages and disadvantages, instruments and surgeon skills requirements. Proper utilization of the «Bikini» and Harding approaches provides good functional results in early and late terms. «Bikini» approach requires a larger volume of preoperative preparation. The absence of fascia lata and periarticular muscles injury due to the «Bikini» approach usage allows reducing of narcotic analgesics prescriptions, intraoperative blood loss and duration of walking with crutches. Good cosmetical scars effects are achieved by the parallelism of skin incision relatively to Langer’s lines. In the early postoperative period the better functional results were marked, early rehabilitation and mild pain syndrome allow to reduce hospital length of stay. The technical complexity of the «Bikini» approach requires operations number more than 30 per year.